KAJIAN KITAB DIRA SA T FI AL-HADI TH WA AL-TARI KH: AH A DITH UMMUL MU'MINI N ‘A ISYAH KARYA MURTAD A AL-‘ASKARI - Mukaromah, Kholila (IAIN Kediri, 2019)
Ã¢â‚¬ËœAisyah wa one of the wives of the Prophet Pbuh. who atrracted much attention. Among the Sunni, he received much praises Ã¢â‚¬â€œfor one thing- because of the breadth and depth of his knowledge, as well as the narration and mastery of his hadith which were considered to be prominent among of the other wives of the Prophet Pbuh. On the contrary, there was a group of people from Shia who instead denounced and cursed Ã¢â‚¬ËœAisha. Starting from this, the author was interested to explore one of the hadith books that tells how the figure of Ã¢â‚¬ËœAisha based on the narration of hadiths compiled by a Shia scholar , Murtad a al-Ã¢â‚¬ËœAskari. The writing of al-Ã¢â‚¬ËœAskari can be counterweight to the Ã¢â‚¬Å“bad imageÃ¢â‚¬Â that has been given by the Shia to Ã¢â‚¬ËœAisha. One interesting view was also conveyed by al-Ã¢â‚¬ËœAskari is that the history of Islam ( from sending of the Prophet Pbuh. to the pledge of Yazid bin MuÃ¢â‚¬â„¢awiyah) can only be truly understood after examining the hadith narration of ummul muÃ¢â‚¬â„¢mini n, Ã¢â‚¬ËœAisha. This research is a literatur review. The discussion of which uses descriptive-analytical method. This paper generally tries to introduce the hadith book titled Dira>sa>t fi al-Hadi th wa al-Tari kh : Aha dith Ummul MuÃ¢â‚¬â„¢mini n Ã¢â‚¬ËœAisha by looking at some general aspects of the composition of the book, including writing background, content, systematic, method, examples of discussion, and also describes the advantages and disadvantages analyzed from several section of the book. Based on the results of the discussion, the author considers that al- Ã¢â‚¬ËœAskari tried to put a description of the figure Ã¢â‚¬ËœAisha objectively based on the historical hadiths that originatedfrom Ã¢â‚¬ËœAisha and also the the other companins (sahabah) about Ã¢â‚¬ËœAisha and the event surrounding herself. In discussing the death of the Prophet Pbuh., al-Ã¢â‚¬ËœAskari included a variety of narration that seems contradictory about the ProphetÃ¢â‚¬â„¢s death moments,Ã¢â‚¬Âwhether in the lap of Ã¢â‚¬ËœAisha or Ã¢â‚¬ËœAli?!Ã¢â‚¬Â. Based on the tarji h method, al- Ã¢â‚¬ËœAskari more favored the narration of hadith which said that the Prophet Pbuh had died in the lap of Ã¢â‚¬ËœAli because more were narrated ( four companions /sahabah). Interestingly, the source of the narration referred to byal-Ã¢â‚¬ËœAskari is almost entirely derived from a number of well-known Sunni scholars. This was done to show how scientific research must be carried out without looking at affiliations of certain religious sects.Keywords : The Narration Hadith of Ã¢â‚¬ËœAisha; Murtad a al-Ã¢â‚¬ËœAskari;The Hadith Book of Shia; the Hadith of the Death ofthe Prophet Pbuh; The Islamic History.